2010
DOI: 10.1051/0004-6361/201013999
|View full text |Cite
|
Sign up to set email alerts
|

The galaxy clusterYSZLXandYSZMrelations from the WMAP 5-yr data

Abstract: We use multifrequency matched filters to estimate, in the WMAP 5-year data, the Sunyaev-Zel'dovich (SZ) fluxes of 893 ROSAT NORAS/REFLEX clusters spanning the luminosity range L X,[0.1−2.4] keV = 2×10 41 −3.5×10 45 erg s −1 . The filters are spatially optimised by using the universal pressure profile recently obtained from combining XMM-Newton observations of the REXCESSsample and numerical simulations. Although the clusters are individually only marginally detected, we are able to firmly measure the SZ signal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 41 publications
(64 reference statements)
12
71
3
Order By: Relevance
“…Despite the large variance between the clusters' assembly histories, we find very little scatter, ∼ 0.2 dex around the Planck2013 mean relation (consistent with other simulations, e.g. Sembolini et al 2013), with only the fossil cluster The Planck data is taken from the 2015 union catalog with rescaled Y 500 = Y 5R500 /1.814 according to Melin et al (2011). Figure 13.…”
Section: X-ray Observablessupporting
confidence: 81%
“…Despite the large variance between the clusters' assembly histories, we find very little scatter, ∼ 0.2 dex around the Planck2013 mean relation (consistent with other simulations, e.g. Sembolini et al 2013), with only the fossil cluster The Planck data is taken from the 2015 union catalog with rescaled Y 500 = Y 5R500 /1.814 according to Melin et al (2011). Figure 13.…”
Section: X-ray Observablessupporting
confidence: 81%
“…2 represent the predictions of a model based on the Y 500 − M 500 relation from Arnaud et al (2010) (Böhringer et al 2007). This calibration is also consistent with WMAP observations (Melin et al 2011) and with the Planck analysis (Planck Collaboration 2011f,g). In each bin we average the model predictions in the same way as the Planck observations: we find the model bin-average redshift-scaled SZ signal as the inverse-errorweighted (pure SZ measurement error) average, assigning each cluster in the bin the same error as the actual observation of that object.…”
Section: Discussionsupporting
confidence: 87%
“…The same procedure is used in Planck Collaboration (2011f). We refer the reader to Melin et al (2006Melin et al ( , 2011 for details.…”
Section: Sz Measurementsmentioning
confidence: 99%
“…This case was strengthened by the WMAP7 data analysis (Komatsu et al 2011) which argues for a deficit of SZ signal, especially at low halo masses. However, re-analysing the same data, Afshordi et al (2007) and Melin et al (2011) found a good agreement between the SZ measurements and X-ray predictions. These conflicting results have demonstrated the need for more precise SZ measurements for larger samples of clusters from dedicated and multi-wavelength surveys in order to improve our understanding of cluster physics and cosmology.…”
Section: Sz Scaling Relations: Pre-survey-era Observationsmentioning
confidence: 66%
“…They have the potential of placing very tight constraints on different classes of dark-energy models, possibly finding signatures of departures from the standard ΛCDM predictions. eROSITA (Predehl et al 2010;Pillepich et al 2012;Merloni et al 2012) will produce cluster catalogs with ∼ 10 5 objects out to redshift ∼1, increasing the current statistical samples by 1-2 orders of magnitude and extending the redshift range over which the growth of cosmic structures can be traced. A number of infrared and optical surveys will provide the required complementary photometric and spectroscopic redshifts, some of which have already started collecting data.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%